조협의 부위에 따른 항산화 전사인자 Nrf2 활성 효과 - 최지연(Jiyeon Choi); 김균하(Kyun Ha Kim); 최준용(Jun Yong Choi); 한창우(Chang Woo Han); 하기태(Ki Tae Ha); 정한솔(Han-Sol Jeong); 주명수(Myungsoo Joo) (동의생리병리학회지, 2014)
The fruit of Gleditsia sinensis has been extensively used as a key ingredient of an herbal remedy for the treatment of various inflammatory diseases in traditional Korean Medicine. However, the reason of using the fruit of G. sinensis for the remedy is unclear. Since Nuclear factor (erythroid-derived 2)-like 2 (Nrf2) is a key anti-inflammatory transcription factor, which is activated by the fruit of G. sinesis, we examined whether other plant parts of G. sinensis are also capable of suppressing inflammatory responses by activating Nrf2. Water extracts of various parts of G. sinensis were prepared and tested for Nrf2 activation by reporter assay and western blot analysis. Our results show that the hull of G. sinensis is the most potent in activating Nrf2. Sequential organic solvent extraction of the hull show that all the fractions had a higher potency in activating Nrf2 than the water extract, albeit differential degrees. The hull originated from Korea in general activated Nrf2 strongly compared to that of China. Chloroform fraction of the hull was further examined, showing that the fraction induced nuclear localization of Nrf2, indicative of activated Nrf2, and Nrf2-dependent gene expression including NAD(P)H dehydrogenase quinone 1 (NQO-1), glutamate-cysteine ligase catalytic subunit (GCLC), and heme oxygenase - 1 (HO-1). Therefore, our results show that, among other plant parts examined in this study, the hull of G. sinensis is the most potent, providing the experimental basis for the use of the hull of G. sinensis as an active ingredient for an anti-inflammatory remedy.